Strategic management of people in the business plan - Souza Capelletto da Cunha, Everton; Fraga das Mercês, Everson; Birk Hansen, Gabriela; Joviniano Alvares dos Prazeres, Paulo (Seven Editora, 2023)
This article aims to show the benefits of deploying strategic management of people into car. To reach those goals several tools used in this system were studied and the most effective ones were selected. For a better understanding, its concepts and benefits were also considered when deployed. By the end of the study a survey was carried out and applied at three car dealership places in Londrina. After that a data analysis was performed and it was followed by a discussion. Through this analysis it was stated that the deployment process for strategic management of people into car dealership places in Londrina is still a slightly evolved issue and it needs some changes. DOI: 10.56238/pacfdnsv1-058